ANALISIS PENGARUH CASH RATIO, GROWTH OF SALES, FIRM SIZE, DAN DEBT TO EQUITY RATIO TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2012) - Catur Wahyu Antoni, 10.05.52.0015; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2014)
The purpose of this research is to analyze the influence of Cash Ratio, Growth of Sale, Firm Size, Debt to Equity Ratio toward Dividend Payout Ratio. The population this research is the companies listed which on the Indonesian Stock Exchange on 2009-2012. The sampling technique is using purposive sampling and obtain the sample of 179 companies. Company data subsequently tested with normality, multicollinearity, autocorrelation and heterokedastisity. Subsequent researchers used multiple regression to determine the relation between those variable. The results showed Cash Ratio, Growth of Sales, Firm Size, Debt to Equity Ratio is a significantly toward Dividend Payout Ratio with the adjustment R2 of 9,8%. Based on the test result it can be concluded that Cash Ratio is not a significant positive effect on Dividend Payout Ratio. Growth of Sales and Firm Size is a significant positive effect on Dividend Payout Ratio. Whereas Debt to Equity Ratio not a significant negative on Dividend Payout Ratio.Keywords: Cash Ratio, Growth Of Sales, Firm Size, Debt to Equity Ratio, Dividend Payout Ratio